Peningkatan Akuntabilitas Personal Mahasiswa Penerima KIP Kuliah UCY melalui Edukasi Literasi Finansial Terintegrasi - Endarwati Endarwati; Citra Ayudiati; Ika Destina Puspita; Supriati Hardi Rahayu; Lutfiani Hidayat (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2026)
This community service activity aims to increase the personal accountability of KIP recipient students studying at Cokroaminoto University Yogyakarta (UCY) through integrated financial literacy education. Using a mixed-methods approach with an explanatory sequential design, data were collected from 34 scholarship recipients. The intervention included comprehensive financial planning workshops, zero-based budgeting training, and the formation of a KIP Kuliah student community. The results demonstrate that integrated financial education significantly enhances students' personal accountability. There is ongoing support so that this program can have an impact on community development for higher education and financial independence.